A novel method to design monolithic catalysts for non-isothermal packed-bed reactors using topology optimisation. (5th March 2023) - Erfani, Navid; Symons, Digby; Fee, Conan; James Watson, Matthew
Highlights: A monolithic catalyst structure is designed using the density-based topology optimisation method. The effects of initial guesses, the energy dissipation constraint, and the Peclet number on the design are investigated. In comparison to a reference honeycomb geometry, the 3D optimised catalyst shows quantitative improvements in terms of pressure drop and conversion. Abstract: This research investigates the application of topology optimisation to the design of monolithic catalysts for packed-bed reactors with endothermic reactions. A reactor model has been developed based on the main assumptions of laminar flow and a first-order reaction. The model includes a catalytic reaction whose rate is determined by a proposed Arrhenius equation along with mass transfer limitations. Using the density-based method, the optimisation problem is formulated as a catalyst distribution problem. The catalyst volume fraction of elements in the discretised design domain determines the geometry of the monolithic structure and consequently the momentum, heat, and mass transfer characteristics of the reactor. By a combination of interpolation functions, continuous material properties and a sufficient penalisation for the intermediate fluid volume fraction values are derived. The Globally Convergent Method of Moving Asymptotes (GCMMA) was employed to solve the optimisation problem. The effects of initial guesses, the energy dissipation constraint, and the Peclet number on the design are investigated in a 2D framework. Then through a 3D optimisation, a complex structure with enhanced mass transfer, thermal, and hydraulic behaviour is developed. Compared to a reference honeycomb geometry with the same catalyst volume fraction, the resulting 3D optimised geometry shows quantitative improvements in terms of the conversion and pressure drop.